Selecting an open-source framework: a practical case based on software development for sensory analysis - Teixeira, Leonor (2015)
The use of frameworks based on Free Open-Source Software (FOSS) has become a viable alternative in the software development process, when compared with Proprietary Software or Closed Source Software. Given that the quality of Open-Source Software (OSS) products varies widely, the careful evaluation of such frameworks, according to a set of requirements, is an important step in the software development process. This work presents the evaluation of some open-source frameworks in order to find the most suitable one for developing a Decision Support System (DSS) to use in Sensory Analysis. This DSS is being designed to support the evaluation of Tasting Panels in sectors where Sensory Analysis is used to assess products’ quality. The methodology used, based on content analysis in Online Collaborative Spaces, proved to be appropriate to achieve the objectives of this study and therefore, can be extended to select OSS in other areas. Thus, the result of this work is valuable not only for researchers on trends in the OSS area, but also for software developers that intend to implement DSS using FOSS.